Thoracic and Lumbar Spine Dissection for Pediatric Deformity - Ravi R. Agrawal, MD; Keith Bridwell, MD; Munish Gupta, MD, MBA; Blake K. Montgomery, MD (Journal of the Pediatric Orthopaedic Society of North America)
The posterior approach to the thoracic and lumbar spine remains the most commonly used method for treating idiopathic scoliosis (IS). A detailed understanding of the relevant anatomy reduces iatrogenic complications, such as durotomy and pneumothorax, while an efficient surgical technique minimizes operative time and blood loss. Few video-based resources detailing step-by-step exposure of the posterior elements are available. Such videos would enhance trainee preparation prior to posterior spinal fusion (PSF) for IS. This technique article reviews the authors’ preferred surgical approach, focusing on the pearls and pitfalls of errant techniques. The intended audience includes orthopaedic surgery and neurosurgery trainees. Additionally, it provides a sample pre-test to evaluate trainee knowledge preoperatively (see Appendix). Key concepts: (1) Subperiosteal dissection after splitting the apophysis is essential to achieving hemostasis. (2) Errant dissection of the thoracic spine can cause durotomy, pneumothorax, and neurologic injury. (3) Supraspinous ligament violation near the UIV can increase the risk of junctional kyphosis. (4) Preserving the UIV and LIV facet joints is essential to maintain adjacent segment joint health. (5) Safe placement of all spinal instrumentation (hooks, screws, and sublaminar fixation) requires adequate spinal exposure.